PENGARUH PEMBELAJARAN SOCCER LIKE GAME TERHADAP KEMAMPUAN BERMAIN SEPAKBOLA - Sujagad, Imam (2016)
PENGARUH PEMBELAJARAN SOCCER LIKE GAME TERHADAP KEMAMPUAN BERMAIN SEPAKBOLA;--- The purpose of this study was to determine whether there is a game like soccer learning effect on the ability to play football at SMAN 2 Banjar. the method used in this study is experimental. The population in this study is that students who are active in extracurricular football, while samples in this study were 40 to 20 people as a control group and an experimental group of 20 people as taken through the consideration of data collection (purposive sampling). This study design pretest and posttest One Group Design. Instruments used GPAI while the treatment is given in the form of training programs like soccer game. The test result data obtained t count numbers playing ability (4.819) and t-table (1.729), it is bigger than t-table on the level of confidence or significance level α = 0.05 with dk (n1-1) = 19 , t1-0,05 price (1,729). Due to the results of t-count is greater than t-table, the test is significant proficiency level. Based on the results of data processing and analysis, concluded that the learning soccer game like a significant effect on the ability to play football in a football lesson.